"I'm Not a Gadget": A Grounded Theory on Unplugging. Issue 5 (20th October 2017) - Morris, Neli; Cravens Pickens, Jaclyn D.
ABSTRACT: Technology has become a pervasive and indispensable part of our lives over the past few decades. Researchers have begun examining the impacts that technology has on individuals as well as on relationships. Although positive outcomes are associated with technology use, a concern about being always connected has motivated individuals to participate in periods of unplugging, with the goal to enhance individual well-being and relationships. Pervasive use of technology means today's therapist will work with clients impacted by the role technology plays in their lives and relationships. The purpose of the present study was to explore the impacts that "unplugging, " or disconnecting from certain types of technology or digital media, would have on individuals and their individual and interpersonal well-being. Using 29 publicly shared stories on blogs, websites, and news articles, the authors presents a theoretical model derived through grounded theory methodology. The theoretical model includes four thematic codes, taking the initial steps, realizing the dependence, regaining time and life, and re-plugging and evaluating the experience, which indicates a progressive process that individuals experience when choosing to unplug. The thematic codes, as well as domains comprising those codes, are presented in a visual format. Future research and clinical implications are discussed.